To find the slope between two points, we can use the slope formula:

6 - 3 / -4 - 2

3 / -6

-0.5

**The slope between those two points is -0.5, or -1/2**

**Answer:**

There is no solution to this problem.

**Step-by-step explanation:**

The 1 digit number cannot be 1, since there would be no remainder.

The 1 digit number cannot be 2, since the remainder could be 0 or 1.

The 1 digit number cannot be 3, since the remainder could be 0, 1, or 2.

So, the 1 digit number must be greater than 3. Let's start with 4. Since the quotient is 307 (remainder 3), 4 x 307 is already more than 3 digits.

**Answer:IDK**

**Step-by-step explanation:IDK**

Hello! So the first thing you want to do is fix the triangles so they are in the same rotation (you can tell which point goes where by matching the points of Trangle PQR to Triangle STU). Next, it’s a matter of addition and subtraction. You add the two known angle measures (46 and 70) and then subtract it from the total degrees a triangle has (180). You should then get 64 as your answer. Hope this helps :)

**Answer:**

**x = 3**

**x = (-1)/2**

**x = 13/4**

**Step-by-step explanation:**

Solve for x:

(2 x)/3 + 15 = 17

Put each term in (2 x)/3 + 15 over the common denominator 3: (2 x)/3 + 15 = (2 x)/3 + 45/3:

(2 x)/3 + 45/3 = 17

(2 x)/3 + 45/3 = (2 x + 45)/3:

1/3 (2 x + 45) = 17

Multiply both sides of (2 x + 45)/3 = 17 by 3:

(3 (2 x + 45))/3 = 3×17

(3 (2 x + 45))/3 = 3/3×(2 x + 45) = 2 x + 45:

2 x + 45 = 3×17

3×17 = 51:

2 x + 45 = 51

Subtract 45 from both sides:

2 x + (45 - 45) = 51 - 45

45 - 45 = 0:

2 x = 51 - 45

51 - 45 = 6:

2 x = 6

Divide both sides of 2 x = 6 by 2:

(2 x)/2 = 6/2

2/2 = 1:

x = 6/2

The gcd of 6 and 2 is 2, so 6/2 = (2×3)/(2×1) = 2/2×3 = 3:

Answer: x = 3

______________________________________________________

Solve for x:

3 x - x + 8 = 7

Grouping like terms, 3 x - x + 8 = (3 x - x) + 8:

(3 x - x) + 8 = 7

3 x - x = 2 x:

2 x + 8 = 7

Subtract 8 from both sides:

2 x + (8 - 8) = 7 - 8

8 - 8 = 0:

2 x = 7 - 8

7 - 8 = -1:

2 x = -1

Divide both sides of 2 x = -1 by 2:

(2 x)/2 = (-1)/2

2/2 = 1:

Answer: x = (-1)/2

_______________________________________

Solve for x:

4 (2 x - 6) = 2

Divide both sides of 4 (2 x - 6) = 2 by 4:

(4 (2 x - 6))/4 = 2/4

4/4 = 1:

2 x - 6 = 2/4

The gcd of 2 and 4 is 2, so 2/4 = (2×1)/(2×2) = 2/2×1/2 = 1/2:

2 x - 6 = 1/2

Add 6 to both sides:

2 x + (6 - 6) = 1/2 + 6

6 - 6 = 0:

2 x = 1/2 + 6

Put 1/2 + 6 over the common denominator 2. 1/2 + 6 = 1/2 + (2×6)/2:

2 x = 1/2 + (2×6)/2

2×6 = 12:

2 x = 1/2 + 12/2

1/2 + 12/2 = (1 + 12)/2:

2 x = (1 + 12)/2

1 + 12 = 13:

2 x = 13/2

Divide both sides by 2:

x = (13/2)/2

2×2 = 4:

Answer: x = 13/4